2020
DOI: 10.1037/mot0000154
|View full text |Cite
|
Sign up to set email alerts
|

Golf coaches’ mindsets about recreational golfers: Gendered golf experiences start on the practice tee.

Abstract: Gender gaps in golf participation persist. Women make up less than 20% of golf’s population in the United Kingdom and United States. Their underrepresentation detrimentally impacts the golf industry, society, and women who are excluded from golf’s well-documented benefits. This article connects theoretical constructs from motivational psychology with issues of gender discrimination in golf. In this article we examine the relationship between golf coaches’ perceptions of recreational women golfers (their mindse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…One’s growth or fixed mindset can impact other people’s behavior and these mindsets can lead to team-level outcomes in the workplace. Mindset researchers have found that managers or employees’ growth mindsets positively correlate to dyadic-level outcomes, such as improved relationships based on feedback and coaching (Gutshall, 2013; Özduran & Tanova, 2017; Rattan & Dweck, 2018; Shapcott & Carr, 2019) and positive influence of managers on their teams (Caniëls et al, 2018; Heslin & VandeWalle, 2008; Wang et al, 2018). Managers or leaders’ mindset can influence others’ behaviors.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One’s growth or fixed mindset can impact other people’s behavior and these mindsets can lead to team-level outcomes in the workplace. Mindset researchers have found that managers or employees’ growth mindsets positively correlate to dyadic-level outcomes, such as improved relationships based on feedback and coaching (Gutshall, 2013; Özduran & Tanova, 2017; Rattan & Dweck, 2018; Shapcott & Carr, 2019) and positive influence of managers on their teams (Caniëls et al, 2018; Heslin & VandeWalle, 2008; Wang et al, 2018). Managers or leaders’ mindset can influence others’ behaviors.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar vein, the coaches’ mindset about their athletes’ abilities is correlated with the behaviors the coaches demonstrate. Particularly, coaches’ prejudice toward women’s golf ability is correlated with negative feedback, resulting in lower player motivation and decreased player performance (Shapcott & Carr, 2019). The researchers found that priming growth mindset, however, effectively reduces coaches bias leading to an increased performance of athletes as well as the amount of participation in golf for recreational purposes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations